Pemulihan Berbasis Solidaritas: Peran Aliansi SUMUT Bersatu Melalui Rumah Aman Peduli Puan dalam Penanganan Kekerasan Seksual - Putri Amelia Sari; Ratih Baiduri; Supsiloani Supsiloani (Universitas Islam Negeri (UIN) Salatiga, 2026)
This study aims to analyze the role of the Peduli Puan Safe House managed by the United North Sumatra Alliance in the recovery process for victims of sexual violence in North Sumatra. This study uses a qualitative method with an ethnographic approach. Data collection techniques were carried out through participant observation, in-depth interviews, and documentation of the safe house managers and victim advocates. This study uses Kimberlé Crenshaw's intersectional feminist theory to understand victims' experiences influenced by relations of power, gender, social class, and patriarchal cultural structures. The results show that the Peduli Puan Safe House not only functions as a temporary shelter, but also becomes a solidarity-based recovery space that provides a sense of physical, psychological, and social security for victims of sexual violence. The forms of recovery provided include psychological assistance, legal assistance, and social recovery through education for the families and surrounding communities of victims. The solidarity built by the United North Sumatra Alliance is seen through empathetic relationships between advocates and victims, emotional support, and efforts to create a more supportive social environment that does not blame the victim. This approach helps victims to reduce trauma, rebuild self-confidence, and dare to fight for their rights in the legal process. This research shows that recovery for victims of sexual violence requires not only professional services but also social support based on solidarity and victim-centeredness.